Ex-ante analysis of the Sorghum and millet improvement program - Anandajayasekeram, P.; Martella, D.R.; Sanders, J.; Kupfuma, B. (CAB International, 2007)
The Southern African Development Community (SADC)/International Crops Research Institute for the Semi-Arid Tropics Sorghum and Millet Improvement Program (SMIP) was started in 1983 as a regional initiative of the SADC in collaboration with one of the International Agricultural Research Centres. This chapter deals with the estimation of the rate of return for the combined investments of the National Agricultural Research System and SMIP. By necessity this study is both ex-ante and ex-post. Two scenarios were considered in the analysis: optimistic and conservative. The differences between the two scenarios were based on the levels of adoption ceiling and yield gains assumed. Seven countries released sorghum varieties and five countries released millet varieties under this collaborative programme. Both the Akino-Hayami method and simple benefit-cost analysis were used. The results revealed that if the appropriate discount rate is 10%, investments in sorghum and millet R&D only paid off if the optimistic estimates are the true representation of the adoption of varieties, the yield gains and the research and transfer cost. The rate of return for this scenario is 14 and that for the conservative scenario is about 5%.